Electrooxidative grafting of amine-terminated dendrimers encapsulating nanoparticles for spatially controlled surface functionalization of indium tin oxide - Lee, Soon Bo; Ju, Youngwon; Kim, Yeoju; Koo, Chong Min; Kim, Joohoon (ROYAL SOC CHEMISTRY, 2013)
We report the electrochemical grafting of amine-terminated dendrimers encapsulating nanoparticles onto indium tin oxide (ITO) surfaces.
Keywords: CARBON ELECTRODES; ADSORPTION; CATALYSIS; PLATINUM; OXYGEN